An assessment of students` portfolio of writing in the English language subject - Hadjirah Raveloarinirina; Asruddin Barori Tou (LingTera, 2017)
The objectives of this study were: (1) to describe the students` portfolios of writing in the English language subject of Kolombo High School of Sleman, Yogyakarta, and (2) to describe the quality of students` portfolios of writing in the English language subject in question. This study used a case study method with a qualitative descriptive approach. The researcher performed data analysis by enriching informationand finding the pattern on the basis of the original data obtained from observation, interview, field notes, and assessment sheet. The result of the research shows that the establishment of the students` Portfolios of writing in English language subject was not appropriately conducted as the portfolio process recommended by the experts due to the limitation of the teacher`s understanding of the assessment criteria, and the analysis of the data collected indicates that the lacks of the students` competences in elaborating the portfolio tasks were due to the limitation of grammar mastery and lacks vocabulary. Nevertheless, the students have improved their writing skills through the drills in elaborating portfolio from time to time.